(untitled) (Conference Zone, 2021)
In today’s large-scale transformation process in all areas of the Action Strategy, it is important to provide the population and the world community with objective and reliable information about events and processes in the country. The national movement supports the process of ensuring the openness of information in society, the rapid development of the national information space and expresses its readiness to support them in every possible way. The media is playing an increasingly important role in shaping public opinion in our country and further enhancing the positive image of Uzbekistan abroad